Prevetion of falls in the elderly in primary care: a systematic review (Research, Society and Development, 2022)
This study aims to gather and analyze evidence on physical therapy actions and interventions applied in primary care in order to prevent the risk of falls in the elderly. This is a systematic review, filed with PROSPERO, carried out in the BVS, PEDro and Scielo databases. The Guidleline Preferred Reporting Items for Systematic Reviews and Meta-Analyses –The PRISMA Statement was used. The research question was: What are the actions and interventions of physical therapy that are applied in primary care to prevent the risk os falls in the elderly? A total of 85 studies were found and, after analysis, seven studies were included in this work. It was possible to verify the diversity of occurrence of studies in their continent of publication namely: South America (n=3), Europe (n=2), Oceania (n=1) and Asia (n=1). As for the level of evidence, the majority (n=4) was level 2 and only three (n=3) had level of evidence 3. There was a consensus that the applicability of preventive measures in primary health care was effective in reducing risk of falls in the elderly, but there was no consensus on the use of a specif protocol. The implementation of training programs and specific exercises performed in primary health care has a significant impact on improving balance, muscle strength, proprioception, functional capacity and quality of life of the elderly assuming an important role in the prevention of falls.